Caracterização e desenvolvimento de um compósito de polietileno verde reforçado com resíduo têxtil - Tirloni, Georgio Enrico (2019)
The textile sector is one of the segments with the greatest negative environmental impact, where solid waste generated by the cutting process represents one of the major problems caused by these industries. This research aimed to develop a composite using textile waste as a reinforcement for high density green polyethylene (HDPE). The work follows the practices of cleaner production in conjunction with project management tools. Cleaner production is present in waste recycling, demonstrating the environmental benefits of the project. Project management was applied to research planning, through the Project Model Canvas tool, assisting in the planning and execution of activities. Through mechanical tests of flexion, traction and impact, three different variables were analyzed: the reinforcement/matrix ratio, where 10, 15 and 20% of mass in fibers were tested; the composition of the residue, evaluating the residues 100% cotton and 70% cotton/30% polyester and; 2 types of processing, hot pressing and injection. For all mechanical analyzes, the increase in properties was gradual to the addition of fibers. With 20% of mass in fibers, the injected material showed 27,03 MPa of flexural strength, 30,94 MPa of tensile strength and 76.44 J/m of impact resistance. In the comparison between the waste compositions, in general, the 100% cotton fabric promoted greater resistance and modules and the residue with polyester increased elongations. In the evaluation of the processing, the hot pressing was superior only in the flexion tests, presenting 30,60 MPa of resistance and 1942 MPa of modulus of elasticity. The cost analysis reiterated that the injection is the most viable process due to the properties presented and the cost for production. The material developed shows potential for future applications, even with the high value of green HDPE, which would increase the price of parts made with the composite by about 8%. The environmental assessment proved to be positive, considering that it met the requirements of cleaner production, as there was the use of recyclable raw material and the material was shown to be able to reduce the environmental impact generated by the textile sector.